2022
DOI: 10.1021/acs.estlett.2c00225
|View full text |Cite
|
Sign up to set email alerts
|

Satellites Detect a Methane Ultra-emission Event from an Offshore Platform in the Gulf of Mexico

Abstract: Mitigation of methane emissions from fossil fuel extraction, processing, and transport is one of the most effective ways to slow global warming. Satellite-based methods are instrumental for the detection, characterization, and quantification of this type of emissions. However, despite the rapid development of satellite-based methane plume detection methods for terrestrial surfaces, there is still an important observational gap with respect to offshore oil and gas infrastructure, which accounts for roughly 30% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 22 publications
(35 reference statements)
2
22
0
Order By: Relevance
“…Potentially large methane sources over water include offshore oil and gas facilities, wastewater facilities, hydroelectric and agricultural reservoirs, and estuaries. They can be observed in the sunglint mode or by lidar (Kiemle et al, 2017;Irakulis-Loitxate et al, 2022b). The wet tropics and the Arctic are a challenge because of persistent cloudiness, compounded in the Arctic by high solar zenith angles and polar darkness and by the collocation of oil and gas emissions with wetland emissions.…”
Section: Discussionmentioning
confidence: 99%
“…Potentially large methane sources over water include offshore oil and gas facilities, wastewater facilities, hydroelectric and agricultural reservoirs, and estuaries. They can be observed in the sunglint mode or by lidar (Kiemle et al, 2017;Irakulis-Loitxate et al, 2022b). The wet tropics and the Arctic are a challenge because of persistent cloudiness, compounded in the Arctic by high solar zenith angles and polar darkness and by the collocation of oil and gas emissions with wetland emissions.…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies have shown the feasibility of quantifying methane point sources from hyperspectral and multispectral missions such as PRISMA (Guanter et al, 2021), Sentinel-2 (S2) (Varon et al, 2021), Landsat-8 (Ehret et al, 2022) and WorldView-3 (Sánchez-García et al, 2021). These recent advances have revealed the existence of large point emissions from O&G production regions (Irakulis-Loitxate et al, 2021, 2022b, coal carbon mines (Guanter et al, 2021) and O&G offshore platforms (Irakulis-Loitxate et al, 2022a).…”
mentioning
confidence: 99%
“…Successful examples of the use of inversions for CH 4 national emissions in large emitters countries for the agriculture and waste and the fossil fuel sectors are given in [ 19 ], and for oil/gas very large leaks of CH 4 , localised in extraction basins and along pipelines by [ 60 ] and ultra-emission events [ 53 ]. Namely, several oil and gas extraction countries like in the Persian Gulf region, Central Asia, and Russia, report significantly less fossil CH 4 emissions than what is constrained by GOSAT-based satellite inversions [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 54 ]) or metrological innovations (e.g., [ 5 ]), NASA's two Orbiting Carbon Observatories arguably set the current technology benchmark, but with poor coverage of the globe on a daily basis [ 15 , 24 ]. For methane, recent missions such as the Italian Space Agency’s PRISMA (Recursore IperSpettrale della Missione Applicativa, [ 14 ]) launched in 2019, the Advanced Hyperspectral Imager (AHSI) aboard the China's GaoFen-5 satellite [ 64 ], launched in 2018, and the GHGsat, launched by the Indian Space Research Organization in 2016 and commercially operated, allow for high-resolution (30–50 m) methane mapping and improved detection of point sources and small plumes [ 40 , 53 , 99 , 100 ].…”
Section: Introductionmentioning
confidence: 99%